Peran Akreditasi dalam Meningkatkan Mutu Pendidikan di SMK Doa Bangsa Palabuhanratu - Komarudin, E.; Qomariyah, Siti; Rahman, Muhamad Atep Saepul; Fauzi, Ari Rahman; Rafli, Muhamad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study is motivated by the importance of accreditation as an instrument for educational quality assurance, especially in vocational schools that are required to produce competent graduates who are ready to compete in the labor market. Accreditation is not only understood as an administrative requirement, but also as an external evaluation mechanism that encourages continuous quality improvement. This study aims to analyze the role of accreditation in improving the quality of education at SMK Doa Bangsa Palabuhanratu. The research employed a descriptive qualitative approach, with data collected through documentation study and literature review of relevant policies, accreditation instruments, and previous research findings. The results indicate that accreditation plays a significant role in improving school management, strengthening the learning process, enhancing teacher professionalism, and developing a sustainable quality culture within the school. The implementation of the Education Unit Accreditation Instrument (IASP) 2020 has also shifted the assessment paradigm from administrative compliance to performance-based and outcome-oriented evaluation. Furthermore, accreditation functions as a driving force in strengthening academic supervision and improving teacher competence in a systematic and continuous manner. In conclusion, accreditation has a strategic role in improving educational quality when it is properly understood and supported by strong commitment and active involvement of all school stakeholders.